2017
DOI: 10.17344/acsi.2017.3166
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating UHPLC-PDA Assay for Simultaneous Determination of Antazoline Hydrochloride and Naphazoline Hydrochloride in Ophthalmic Formulations

Abstract: In the present study, a newly developed method based on ultrahigh performance liquid chromatography (UHPLC) was optimized for the simultaneous determination of antazoline hydrochloride (ANZ) and naphazoline hydrochloride (NFZ) in ophthalmic formulations. Isocratic separation of ANZ and NFZ was performed at 40 °C with an ACE Excel 2 C18-PFP column (2 μm, 2.1 × 100 mm) at a flow rate of 0.6 mL min -1 whereas the mobile phase consisted of acetonitrile/phosphate buffer (60:40, v/v, pH 3.0) containing 0.5% triethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It is an official drug in the US (USP) 9 and British (BP) 10 pharmacopeias where its assay was performed by HPLC methods. Moreover, BP reports four official impurities; A, B, C and D. Literature review revealed that NPZ has been determined either in bulk powder or in presence with other drugs using several techniques including; spectrophotometry, [11][12][13][14][15][16][17][18][19][20] HPLC, [21][22][23][24][25][26][27][28][29][30][31][32] TLC 33 and capillary electrophoresis. [34][35][36][37][38][39][40] Pheniramine maleate (PHN) is an antihistaminic drug with anticholinergic properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is an official drug in the US (USP) 9 and British (BP) 10 pharmacopeias where its assay was performed by HPLC methods. Moreover, BP reports four official impurities; A, B, C and D. Literature review revealed that NPZ has been determined either in bulk powder or in presence with other drugs using several techniques including; spectrophotometry, [11][12][13][14][15][16][17][18][19][20] HPLC, [21][22][23][24][25][26][27][28][29][30][31][32] TLC 33 and capillary electrophoresis. [34][35][36][37][38][39][40] Pheniramine maleate (PHN) is an antihistaminic drug with anticholinergic properties.…”
Section: Introductionmentioning
confidence: 99%